Rapidly-formed bentonite-based blocking and controlling material and preparation method thereof
By using bentonite, fly ash, blast furnace slag and exciter, the problems of high construction costs, poor anti-seepage performance and high construction difficulty in the existing technology are solved, and high strength and low cost are achieved and fast blocking effect.
Patent Information
- Application Number
- CN202411436286.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing pollution site barrier technology has problems such as high construction cost, poor anti-seepage performance, weak walls and easy cracks, as well as high construction difficulty and high cost, making it difficult to achieve rapid resistance and efficient anti-seepage.
The rapid-forming resistive material made of bentonite, fly ash, blast furnace slag and exciter is prepared by ball milling, sieving, drying, stirring and mixing, and water bath ultrasonic dissolution to form high-strength and low-cost resistive material. .
It realizes rapid molding, high-strength and low-cost resistive materials, improves anti-seepage performance, reduces construction difficulty and cost, and is suitable for rapid resistive control of polluted sites.
Smart Images

Figure CN119430706A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a rapidly formed bentonite-based barrier control material and a preparation method thereof, belonging to the technical field of barrier control of polluted sites. Background Art
[0002] In recent years, the chemical industry has developed rapidly. Whether it is chemical explosions or leaks caused by accidents, or a large number of old industrial sites left behind by the transformation and relocation of industrial enterprises, they will cause serious pollution to the soil and groundwater of the original sites. Especially for major environmental emergencies that require emergency treatment, if effective measures cannot be taken in a short period of time to prevent the spread of pollution, these high-concentration pollutants will spread rapidly in the environmental medium, causing more serious impacts on the natural environment and the safety of people's lives and property. Therefore, it is very important to develop a material that can be quickly formed and effectively block pollutants.
[0003] At present, the most widely used method in the field of pollution site control technology is cement-based control materials. Traditional cement barrier walls have high construction costs and poor anti-seepage performance. The overall performance of the barrier wall is easily affected by high concentrations of pollutants and greatly reduced. Compared with cement-based barrier walls, soil-bentonite barrier walls are more economical, but the wall is weak and prone to shrinkage cracks, which greatly reduces the wall's control effect. Although the HDPE geomembrane barrier wall has good anti-seepage performance, it is difficult to construct, the cost is high, and the construction period is long. Therefore, it is urgent to develop a barrier wall material that can achieve rapid control, has high bentonite wall strength, low cost, and outstanding anti-seepage performance. Summary of the invention
[0004] Purpose of the invention: The first purpose of the present invention is to provide a high-strength bentonite-based resistance control material that can be rapidly formed. The second purpose of the present invention is to provide a method for preparing the rapidly formed bentonite-based resistance control material.
[0005] Technical solution: The rapid-forming bentonite-based resistance control material described in the present invention is made of the following raw materials: bentonite, fly ash, blast furnace slag and activator, wherein the mass ratio of bentonite to fly ash is 1:0.2-0.4, the added amount of blast furnace slag is 10-20% of the total mass of bentonite and fly ash, and the added amount of activator is 13.33-16.69% of the total mass of bentonite and fly ash.
[0006] Preferably, the mass ratio of bentonite to fly ash is 1:0.2.
[0007] Preferably, the amount of blast furnace slag added is 15% of the total mass of bentonite and fly ash.
[0008] Preferably, the added amount of the activator is 14.21% of the total mass of the bentonite and the fly ash.
[0009] Preferably, the bentonite is calcium-based bentonite with a mesh size of 40 to 300.
[0010] Preferably, the fly ash is primary steel slag or high calcium fly ash, preferably fly ash #4, primary steel slag or fly ash #1.
[0011] Preferably, the blast furnace slag is S105 grade slag powder.
[0012] Preferably, the activator solution is prepared by dissolving water glass and sodium hydroxide in deionized water and then adding a modifier.
[0013] More preferably, the modifier is a phosphate substance.
[0014] More preferably, the phosphate substance is one or more of dihydrogen phosphate, hexametaphosphate, tripolyphosphate or pyrophosphate.
[0015] More preferably, the modulus of the water glass is 2.4.
[0016] More preferably, the mass ratio of water glass to sodium hydroxide is 16.8:0.473-2.365, preferably 16.8:1.689, and the mass ratio of water glass to modifier is 16.8:1.4-4.2, preferably 16.8:1.4.
[0017] A method for preparing the rapid prototyping bentonite-based resistance control material of the present invention comprises the following steps:
[0018] (1) ball-milling, sieving and drying bentonite, fly ash and blast furnace slag respectively;
[0019] (2) mixing the fly ash obtained in step (1) with blast furnace slag to obtain a dry powder sample;
[0020] (3) dissolving water glass and sodium hydroxide in deionized water, dissolving them in a water bath with ultrasonic wave, adding a modifier, and continuing to dissolve them in a water bath with ultrasonic wave, stirring in a water bath, and aging to obtain an activator;
[0021] (4) adding the stimulant obtained in step (3) to the dry powder sample in step (2), stirring, and stewing to obtain a slurry;
[0022] (5) Add the bentonite obtained in step (1) to the slurry obtained in step (4), stir rapidly, pour into a mold for forming, and allow to cure naturally.
[0023] Preferably, in step (1), the ball milling time is 6 to 8 hours, the product is sieved through a 40 to 200 mesh sieve, the drying temperature is 95 to 110° C., and the drying time is 24 to 36 hours.
[0024] Preferably, in step (2), the stirring and mixing time is more than 10 minutes.
[0025] Preferably, in step (3), the temperature of the water bath is 35-45° C., the time for ultrasonic dissolution in the water bath is 8-15 min, the time for ultrasonic dissolution in the water bath is continued to be 10-30 min, the time for stirring in the water bath is 8-15 min, and the time for aging is 20-50 min.
[0026] Preferably, in step (4), the stirring time is 5 to 10 minutes, and the stewing time is 2 to 10 minutes.
[0027] Preferably, in step (5), the rapid stirring time is 8 to 10 minutes.
[0028] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0029] (1) The main materials used in the present invention are calcium-based bentonite and industrial solid waste fly ash, which are very abundant in domestic reserves. Compared with traditional cement-based barrier control materials, they are greener and more low-carbon and reasonably realize the resource utilization of solid waste. At the same time, the production cost is further reduced, achieving the advantages of cost reduction and efficiency improvement.
[0030] (2) The barrier control material activator of the present invention performs joint activation modification on the bentonite-fly ash #1-blast furnace slag mixture. In an alkaline environment, the glass in the mixture dissolves Si-O-Si and breaks, and finally forms hydrated gelled products such as CSH, CAH and CASH. These hydrated gelled products greatly improve the overall compressive strength of the bentonite-based barrier control material, and also make the barrier control material more stable as a whole and more adaptable to the external environment of dry-wet cycles, thereby improving the universality of barrier control and solving the problem of weak soil-bentonite barrier wall;
[0031] (3) The barrier control material activator in the present invention needs to be stirred and mixed with blast furnace slag and fly ash first. The activator directly acts on the solid waste mixture to make it fully stimulated and dissolved (solid waste particles can be well stimulated and dissolved when the pH value is greater than 12. When calcium-based bentonite is added to the activator together with the solid waste mixture, the pH of the activator will be reduced and the activator part will be combined with the calcium-based bentonite, thereby affecting the stimulation and dissolution of the solid waste mixture, resulting in a decrease in the overall performance of the material). After the simmering is completed, calcium-based bentonite is added and mixed to finally form a bentonite-based barrier control material with excellent performance.
[0032] (3) The present invention modifies the activator formed by water glass and sodium hydroxide by dissolving the modifier phosphate substance in the barrier control material activator, thereby obtaining a modified activator with a more superior activating effect, thereby further improving the overall performance of the bentonite-based barrier control material.
[0033] (4) The present invention uses phosphate-based modifiers dissolved in the barrier material activator to increase the double layer thickness of bentonite particles, separate bentonite aggregates, and reduce pore size through ion exchange, chemical adsorption, and steric stabilization, thereby forming a modified calcium-based bentonite with higher expansibility, good dispersibility, and impermeability. The expansion performance of bentonite is further improved (modification and alkali excitation must be carried out simultaneously, otherwise a dense internal structure cannot be formed). At the same time, the bentonite structure is filled in the pores of the hydrated gelling material after absorbing water. The modified bentonite fully fills each pore during the expansion process, and under the dual effects of the hydration gel skeleton constraint and the expansion of bentonite, the interior of the barrier material gradually densifies. Therefore, the impermeability of the barrier material is greatly improved, which is 1x10 higher than the value specified in the national standard. -11 cm / s decreased by two orders of magnitude.
[0034] (5) The high-strength bentonite-based resistance-control material provided by the present invention that can be quickly resisted has good chemical compatibility, acid and alkali resistance, and high salt resistance.
[0035] (6) The preparation method of the high-strength bentonite-based barrier material with rapid barrier control provided by the present invention has a simple process and a wide range of applicable processes. It can be used as a vertical barrier material and as a horizontal barrier material.
[0036] (7) The present invention uses water glass, phosphate and the like as activators and modifiers, and uses industrial solid waste as admixtures to supplement the required elements such as calcium, silicon and aluminum. The obtained barrier control material has good compressive strength and good chemical compatibility, and can achieve rapid barrier control function. The permeability after curing for 7 days reaches 0.97ⅹ10 -9 cm / s, which is two orders of magnitude lower than the national standard requirement. Its unconfined compressive strength can reach 0.93MPa after 24h of curing, 2.5MPa after 3d of curing, and 8.8MPa after 28d of curing. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a general flow chart of a method for preparing a rapid-prototyping bentonite-based resistance control material according to the present invention. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0039] The fly ash #1 used in the following experiments was purchased from Guyue Mineral Products Co., Ltd., and the other fly ashes were purchased from Hebei Zongrun Mineral Products Co., Ltd. All fly ash types, components and contents of each component are shown in Table 1 below;
[0040] The blast furnace slag is S105 grade slag powder purchased from Lingshou County Dehang Mineral Products Co., Ltd., and the component contents are shown in Table 1 below;
[0041] Calcium-based bentonite was purchased from Zhenjiang Mufeng Bentonite Company with a particle size of 40 to 200 meshes.
[0042] Steel slag was purchased from Gongyi Yuanheng Water Purification Material Factory.
[0043] 2.4-mode water glass was purchased from Tianjin Huasheng Chemical Reagent Co., Ltd.
[0044] Analytical grade sodium hexametaphosphate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0045] Analytical grade sodium hydroxide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0046] Table 1 Types of fly ash, component content and content of each component (%)
[0047]
[0048] Note: Fly ash #1 is gray-green high-calcium fly ash, fly ash #2 is gray low-calcium fly ash, fly ash #3 is black low-calcium fly ash, and fly ash #4 is white high-calcium fly ash.
[0049] Example 1
[0050] 1. According to the mass percentage of calcium bentonite: fly ash #1 of 1:0.2, 116.67g of calcium bentonite and 23.33g of fly ash #1 are taken respectively, totaling 140g. The amount of blast furnace slag added is 15% of the total amount of calcium bentonite and fly ash #1 of 140g, the amount of 2.4 modulus water glass is 12% of the total amount of calcium bentonite and fly ash #1 of 140g, the amount of analytical pure sodium hydroxide is 1.206% of the total amount of calcium bentonite and fly ash #1 of 140g, and the amount of sodium hexametaphosphate is 1% of the total amount of calcium bentonite and fly ash #1 of 140g.
[0051] Among them, calcium-based bentonite, fly ash #1 and blast furnace slag were first subjected to high-temperature drying treatment at 105°C, and then ground using a planetary ball mill and ground at high speed for 6 hours. The ground samples were taken out and sieved through 200 mesh, and the unsieved coarse particles were subjected to secondary high-speed grinding and sieving. The collected 200-mesh samples were dried again at 105°C for 24 hours to obtain calcium-based bentonite, fly ash #1 and blast furnace slag powder samples, respectively.
[0052] The accurately weighed GGBS and fly ash #1 powder were uniformly mixed in a blender for 10 minutes to obtain a dry powder sample. A determined mass of 2.4 mode water glass was added to 70 mL of ultrapure water for dissolution, and an accurately weighed amount of analytically pure sodium hydroxide was added at the same time. Ultrasonic dispersion was performed in 40°C water and proper stirring was performed with the aid of a glass rod until all dissolved. Then, an accurately weighed amount of analytically pure sodium hexametaphosphate was added. The sodium hydroxide and sodium hexametaphosphate were dissolved with a large amount of heat, which promoted the interaction between sodium hydroxide, sodium hexametaphosphate and 2.4 mode water glass. Ultrasonic crushing and dissolution were performed in an ultrasonic instrument at 40°C for 10 minutes, and then ultrasonic dispersion and dissolution were performed in a water bath for 10 minutes and stirred with a glass rod. The mixture was stirred with the aid of a glass rod until it was completely dissolved, and then magnetically stirred at 40°C (800 r / min) for 5 minutes. After the solution was completely dissolved, it was aged at room temperature for 30 minutes. Finally, the stirred resistance control material excitation solution was poured into a stirrer and mixed with the dry powder sample. After stirring for 10 minutes, the weighed calcium-based bentonite was added to the slurry and continued to stir for 10 minutes. After stirring evenly, it was stuffed for 8 minutes. Finally, it was poured into a circular mold (inner diameter 50 mm, height 50 mm) and cured to obtain the bentonite-based resistance control material, which was naturally cured for 24 hours and 72 hours. The preparation process is as follows: Figure 1 shown.
[0053] 2. Take calcium-based bentonite and fly ash #1 according to the mass percentage of calcium-based bentonite: fly ash #1 of 1:0, 1:0.4, 1:0.6, and 1:1, and keep the masses of other components unchanged in step 1. Repeat the experimental process of step 1 above to obtain 4 groups of bentonite-based barrier control materials, and naturally cure them for 24h and 72h.
[0054] The unconfined compressive strength test of the bentonite-based resistance control materials obtained from the above five groups of experiments after natural curing for 24 hours and 72 hours was carried out. The performance test results are shown in Table 2. (Unconfined compressive strength = pressure / stress area)
[0055] Table 2 Unconfined compressive strength of bentonite-based resistance control materials prepared with different mass percentages of calcium-based bentonite and fly ash
[0056] Proportion 1:0 1:0.2 1:0.4 1:0.6 1:1 1 day unconfined compressive strength (Pa) 715820.3 930439.2 754273.9 651193.7 626809.3 3-day unconfined compressive strength (Pa) 1386233 2496075.5 1972445.5 1701261.3 1408967
[0057] It can be seen from Table 2 that with the increase of the mass percentage of calcium-based bentonite and fly ash #1, the unconfined compressive strength shows a trend of first increasing and then decreasing. When the mass percentage of calcium-based bentonite and fly ash #1 is in the range of 1:0-0.4, its one-day unconfined compressive strength is good, and the one-day unconfined compressive strength exceeds 0.73MPa, especially when the ratio is 1:0.2, its one-day unconfined compressive strength is as high as 0.93MPa, and by 3 days, The mass percentage of calcium-based bentonite to fly ash #1 is 1:0, that is, the unconfined compressive strength without adding fly ash #1 is significantly lower, while the unconfined compressive strength of calcium-based bentonite to fly ash #1 is 1:0.2-0.4, which is still good. It can be seen that the mass percentage of calcium-based bentonite to fly ash #1 is 1:0.2-0.4, which is more suitable, and the optimal is 1:0.2. Its 1-day unconfined compressive strength and 3-day unconfined compressive strength are far higher than other groups.
[0058] Example 2
[0059] The experimental process is the same as that of Example 1, wherein the mass ratio of calcium-based bentonite to fly ash is 1:0.2, a total of 140g, the amount of blast furnace slag added is 15% of the total amount of calcium-based bentonite and fly ash 140g, the amount of 2.4-mode water glass is 12% of the total amount of calcium-based bentonite and fly ash 140g, the amount of analytical pure sodium hydroxide is 1.206% of the total amount of calcium-based bentonite and fly ash 140g, and the amount of sodium hexametaphosphate is 1% of the total amount of calcium-based bentonite and fly ash 140g, wherein the fly ashes are fly ash #2, fly ash #3, fly ash #4, first-grade steel slag, and second-grade steel slag. Comparison with the same amount of fly ash #1 in Example 1 is made to prepare bentonite-based resistance control materials, and natural curing is performed for 72h. The unconfined compressive strength test is the same as in Example 1, and the results are shown in Table 3.
[0060] Table 3 Unconfined compressive strength of bentonite-based resistance control materials prepared with different fly ash
[0061]
[0062]
[0063] It can be seen from Table 3 that only fly ash #4, primary steel slag, secondary steel slag and fly ash #1 used in Example 1 have a 1-day unconfined compressive strength higher than 0.71 MPa, and the other two unconfined compressive strengths are significantly lower. After 3 days, the unconfined compressive strength of secondary steel slag is much lower than those of fly ash #4, primary steel slag and fly ash #1 used in Example 1. It can be seen that fly ash #4, primary steel slag and fly ash #1 are better choices for fly ash, especially the unconfined compressive strength of fly ash #1 used in Example 1 from 1 to 3 days exceeds that of other groups.
[0064] Example 3
[0065] The experimental process is the same as that of Example 1, wherein the mass ratio of calcium-based bentonite to fly ash #1 is 1:0.2, a total of 140g, the amount of blast furnace slag added is 15% of the total amount of calcium-based bentonite and fly ash #1 of 140g, the amount of 2.4-mode water glass is 12% of the total amount of calcium-based bentonite and fly ash #1 of 140g, the amount of analytical pure sodium hydroxide is 1.206% of the total amount of calcium-based bentonite and fly ash #1 of 140g, and the amount of sodium hexametaphosphate is 1% of the total amount of calcium-based bentonite and fly ash #1 of 140g. The difference is that the addition time of sodium hexametaphosphate is different during the preparation process, and the specific steps are as follows:
[0066] The accurately weighed GGBS and fly ash #1 powder were uniformly mixed in a blender for 10 minutes to obtain a dry powder sample. Then, the accurately weighed sodium hexametaphosphate and calcium-based bentonite powder were dry-mixed to obtain a mixed sample. Add a certain mass of 2.4-mode water glass to 70 mL ultrapure water for dissolution, and add an accurately weighed amount of analytical pure sodium hydroxide, ultrasonically disperse in 40°C water and stir appropriately with the aid of a glass rod until it is completely dissolved. The sodium hydroxide dissolves and releases a lot of heat, which promotes the interaction between sodium hydroxide and 2.4-mode water glass. Perform 10 minutes of ultrasonic crushing and dissolution at 40°C in an ultrasonic instrument and stir with the aid of a glass rod until it is completely dissolved, then perform 5 minutes of magnetic stirring at 40°C (800 r / min), and age at room temperature for 30 minutes after dissolution. Finally, pour the stirred resistance control material excitation solution into a stirrer and mix it with the dry powder sample. After stirring for 10 minutes, add the weighed calcium-based bentonite to the slurry and continue stirring for 10 minutes. After stirring evenly, suffocate for 8 minutes, and finally pour it into a circular mold (inner diameter 50 mm, height 50 mm) for curing and molding to obtain a bentonite-based resistance control material, which is naturally cured for 24 hours and 72 hours. The unconfined compressive strength test is the same as in Example 1, and the results are shown in Table 4.
[0067] Example 4
[0068] The experimental process is the same as that of Example 1, wherein the mass ratio of calcium-based bentonite to fly ash #1 is 1:0.2, a total of 140g, the amount of blast furnace slag added is 15% of the total amount of calcium-based bentonite and fly ash #1 of 140g, the amount of 2.4-mode water glass is 12% of the total amount of calcium-based bentonite and fly ash #1 of 140g, the amount of analytical pure sodium hydroxide is 1.206% of the total amount of calcium-based bentonite and fly ash #1 of 140g, and the amount of sodium hexametaphosphate is 1% of the total amount of calcium-based bentonite and fly ash #1 of 140g. The difference is that the addition time of calcium-based bentonite is different during the preparation process, and the specific steps are as follows:
[0069] Accurately weighed hot GGBS, hot fly ash #1 and calcium-based bentonite powder were uniformly mixed in a blender for 10 minutes to obtain a dry powder sample. A determined mass of 2.4 mode water glass was added to 70 mL of ultrapure water for dissolution, and an accurately weighed amount of analytically pure sodium hydroxide was added at the same time. The mixture was ultrasonically dispersed in 40°C water and stirred appropriately with the aid of a glass rod until all the mixture was dissolved. An accurately weighed amount of analytically pure sodium hexametaphosphate was then added. The sodium hydroxide and sodium hexametaphosphate dissolved and released a large amount of heat, which promoted the interaction between sodium hydroxide, sodium hexametaphosphate and 2.4 mode water glass. The mixture was ultrasonically crushed and dissolved at 40°C in an ultrasonic instrument for 10 minutes, and then ultrasonically dispersed and dissolved in a water bath for 10 minutes with the aid of a glass rod until all the mixture was dissolved. Then, magnetic stirring at 40°C (800 r / min) was performed for 5 minutes. After the mixture was dissolved, it was aged at room temperature for 30 minutes. Finally, the stirred resistance control material excitation solution was poured into a stirrer and mixed with the dry powder sample. After stirring for 10 minutes, the mixture was stuffed for 8 minutes. Finally, the mixture was poured into a circular mold (inner diameter 50 mm, height 50 mm) for curing and molding to obtain a bentonite-based resistance control material, which was naturally cured for 24 hours and 72 hours. The 1-day and 3-day unconfined compressive strength tests were the same as in Example 1, and the results are shown in Table 4.
[0070] Table 4 Unconfined compressive strength of sodium hexametaphosphate or calcium-based bentonite added at different times
[0071] Preparation method Example 1 Example 3 Example 4 1 day unconfined compressive strength (Pa) 930439.2 788899.2 711995.6 3-day unconfined compressive strength (Pa) 2496075.5 2047142.9 1916693.1
[0072] As can be seen from Table 4, although the unconfined compressive strength of the bentonite-based resistance control material prepared by adding sodium hexametaphosphate or calcium-based bentonite at different times can be greater than 0.71MPa, the unconfined compressive strength of 1 added by sodium hexametaphosphate to the resistance control material excitation solution is increased by 0.14MPa compared with that added directly to calcium-based bentonite, and the unconfined compressive strength of the bentonite-based resistance control material prepared by directly mixing calcium-based bentonite with GGBS and fly ash #1 is significantly reduced by more than 0.22MPa even if sodium hexametaphosphate is added to the resistance control material excitation solution, indicating that the addition time of sodium hexametaphosphate and calcium-based bentonite has a significant effect on the performance of the prepared bentonite-based resistance control material. The acid-base test of the material showed that the pH value of the material in Example 1 is 12.39, the pH value of the material in Example 3 is 11.34, and the pH value of the material in Example 4 is 10.93.
[0073] Example 5
[0074] The experimental process is the same as that of Example 1, wherein the mass ratio of calcium bentonite to fly ash #1 is 1:0.2, totaling 140 g, the addition amount of blast furnace slag is 0%, 5%, 10%, 20% and 25% of the total amount of calcium bentonite and fly ash #1 140 g, respectively, the amount of 2.4-mode water glass is 12% of the total amount of calcium bentonite and fly ash #1 140 g, the amount of analytical pure sodium hydroxide is 1.206% of the total amount of calcium bentonite and fly ash #1 140 g, and the amount of sodium hexametaphosphate is 1% of the total amount of calcium bentonite and fly ash #1 140 g. The unconfined compressive strength test is the same as that of Example 1, and the results are shown in Table 5.
[0075] Table 5 Unconfined compressive strength measured at different times with different GGBS addition amounts
[0076]
[0077]
[0078] It can be seen from Table 5 that within 1-3 days, with the increase of GGBS addition, the unconfined compressive strength of the prepared bentonite-based resistance-control material first increases and then decreases. When the GGBS addition is 10-20%, the 1-day unconfined compressive strength of the prepared bentonite-based resistance-control material can exceed 0.74MPa. After 3 days, when the GGBS addition is 10-20%, the unconfined compressive strength of the prepared bentonite-based resistance-control material can exceed 1.78MPa, which is higher than other addition amounts, indicating that it is more appropriate to control the GGBS addition amount to 10-25%, and the best effect is achieved at 15%.
[0079] Example 6
[0080] The experimental process is the same as that of Example 1, wherein the mass ratio of calcium bentonite to fly ash #1 is 1:0.2, totaling 140 g, the amount of blast furnace slag added is 15% of the total amount of calcium bentonite and fly ash #1, 140 g, the amount of 2.4-mode water glass is 12% of the total amount of calcium bentonite and fly ash #1, 140 g, the amount of analytical pure sodium hydroxide is 1.206% of the total amount of calcium bentonite and fly ash #1, and the amount of sodium hexametaphosphate is 0%, 1%, 2%, 3%, 4% and 5% of the total amount of calcium bentonite and fly ash #1, 140 g. The unconfined compressive strength test is the same as that of Example 1, and the results are shown in Table 6.
[0081] Table 6 Unconfined compressive strength measured at different times with different sodium hexametaphosphate addition amounts
[0082]
[0083] As can be seen from Table 6, within 1-3 days, with the increase of the amount of sodium hexametaphosphate added, the unconfined compressive strength of the prepared bentonite-based resistance control material first increased and then decreased. And within 1 day, when the amount of GGBS added was 1-3%, the unconfined compressive strength of the prepared bentonite-based resistance control material could exceed 0.79MPa. After 3 days, when the amount of GGBS added was 1-3%, the unconfined compressive strength of the prepared bentonite-based resistance control material could exceed 2MPa, which was higher than other addition amounts, indicating that it is more appropriate to control the amount of GGBS added at 1-3%, and the best effect is achieved at 1%.
[0084] Example 7
[0085] The experimental process is the same as that of Example 1, wherein the mass ratio of calcium bentonite to fly ash #1 is 1:0.2, a total of 140 g, the amount of blast furnace slag added is 15% of the total amount of calcium bentonite and fly ash #1 of 140 g, the amount of 2.4-mode water glass is 12% of the total amount of calcium bentonite and fly ash #1 of 140 g, and the amount of sodium hexametaphosphate is 0%, 1%, 2%, 3%, 4% and 5% of the total amount of calcium bentonite and fly ash #1 of 140 g. The unconfined compressive strength test is the same as that of Example 1, and the results are shown in Table 6. To more accurately obtain the best dosage of sodium hydroxide, the dosage is calculated according to the ratio of SiO2 / Na2O. The amount of analytical pure sodium hydroxide is set to 0 gram, 0.215 gram, 0.473 gram, 0.788 gram, 1.182 gram, 1.689 gram, 2.365 gram, 3.311 gram, respectively, that is, the amount of analytical pure sodium hydroxide is 0, 0.154%, 0.338%, 0.563%, 0.844%, 1.206%, 1.689%, 2.365% of the total amount of 140g of calcium bentonite and fly ash #1. The result is shown in Table 7.
[0086] Table 7 Effect of different SiO2 / Na2O values of resistance control material activators on unconfined compressive properties
[0087]
[0088] As can be seen from Table 7, within 1-3 days, the unconfined compressive strength of the prepared bentonite-based resistance control material first increased and then decreased with the increase in the mass ratio of water glass to sodium hydroxide. And within 1 day, when the mass ratio SiO2 / Na2O was 1.2-2.0, the unconfined compressive strength of the prepared bentonite-based resistance control material could exceed 0.84MPa. After 3 days, when SiO2 / Na2O was 1.2-2.0, the unconfined compressive strength of the prepared bentonite-based resistance control material could exceed 2MPa, which was higher than other addition amounts, indicating that it is more appropriate to control the mass ratio of SiO2 to Na2O at 1.2-2.0, and the best effect is achieved when the mass ratio is 1.4, at which time the amount of sodium hydroxide added is 1.689g.
[0089] Example 8
[0090] The experimental process is the same as that of Example 1, wherein the molding mold is changed to a ring cutter with an edge, and the test is carried out according to the test method in the industry standard JTG 3430-2020 "Highway Geotechnical Test Code" - variable head permeability test, the inner diameter of the ring cutter is 61.8mm, and the height is 40mm; the permeability coefficient of the permeable stone should be greater than 1×10-3cm / s. Variable head permeability coefficient calculation formula:
[0091]
[0092] Where k t is the permeability coefficient of the sample at t℃ (cm / s), a is the inner diameter area of the variable head pipe (cm 2 ), L is the sample height, H1 is the starting head, H2 is the ending head, A is the cross-sectional area of the water flow (cm 2 ). The results are shown in Table 8.
[0093] Table 8 Permeability of bentonite-based barrier control materials at different curing times (national standard: 1×10 -7 cm / s)
[0094]
[0095] As can be seen from Table 8, this embodiment tests the permeability of bentonite-based barrier control materials under different curing times. Among them, the initial permeability coefficient (permeability 6h) of the bentonite-based barrier control material reaches 4.47×10 -8 cm / s, which is one order of magnitude lower than the national standard. After 7 days of curing, the permeability parameter reached 6.76×10 -9 cm / s, which is two orders of magnitude lower than the national standard. Even after 7 days of penetration, the penetration parameter can reach 1.1×10 -9 cm / s, which is two orders of magnitude lower than the national standard, so this material can be used in some sudden emergency control scenarios. It can be seen that with the increase of curing time, the permeability coefficient further decreases. When the permeation is 28 days, the minimum permeability coefficient can reach 0.97×10 -9 cm / s, which is two orders of magnitude lower than the national standard, indicating that bentonite-based barrier control materials have excellent anti-seepage performance.
Claims
1. A rapid-prototyping bentonite-based resistance control material, characterized in that: The invention comprises the following raw materials: bentonite, fly ash, blast furnace slag and activator, wherein the mass ratio of bentonite to fly ash is 1:0.2-0.4, the added amount of blast furnace slag is 10-20% of the total mass of bentonite and fly ash, and the added amount of activator is 13.33-16.69% of the total mass of bentonite and fly ash.
2. The rapid prototyping bentonite-based resistance control material according to claim 1, characterized in that: The bentonite is calcium-based bentonite with a mesh size of 40 to 300.
3. The rapid prototyping bentonite-based resistance control material according to claim 1, characterized in that: The fly ash is first-grade steel slag or high-calcium fly ash, and the blast furnace slag is S105 grade slag powder.
4. The rapid prototyping bentonite-based resistance control material according to claim 1, characterized in that: The activator solution is prepared by dissolving water glass and sodium hydroxide in deionized water and then adding a modifier.
5. The rapid prototyping bentonite-based resistance control material according to claim 4, characterized in that: The modifier is a phosphate substance.
6. The rapid prototyping bentonite-based resistance control material according to claim 5, characterized in that: The phosphate substance is one or more of dihydrogen phosphate, hexametaphosphate, tripolyphosphate or pyrophosphate.
7. The rapid prototyping bentonite-based resistance control material according to claim 4, characterized in that: The modulus of the water glass is 2.4, the mass ratio of the water glass to sodium hydroxide is 16.8:0.473-2.365, and the mass ratio of the water glass to the modifier is 16.8:1.4-4.
2.
8. A method for preparing the rapid prototyping bentonite-based resistance control material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) ball-milling, sieving and drying bentonite, fly ash and blast furnace slag respectively; (2) mixing the fly ash obtained in step (1) with blast furnace slag to obtain a dry powder sample; (3) dissolving water glass and sodium hydroxide in deionized water, dissolving them in a water bath by ultrasonication, adding a modifier and continuing to dissolve them in a water bath by ultrasonication, stirring in a water bath, and aging to obtain an activator; (4) adding the stimulant obtained in step (3) to the dry powder sample in step (2), stirring, and stewing to obtain a slurry; (5) Add the bentonite obtained in step (1) to the slurry obtained in step (4), stir rapidly, pour into a mold for forming, and allow to cure naturally.
9. The preparation method according to claim 8, characterized in that: In step (1), the ball milling time is 6 to 8 hours, the mixture is sieved through a 40 to 200 mesh sieve, the drying temperature is 95 to 110° C., and the drying time is 24 to 36 hours; in step (2), the stirring and mixing time is more than 10 minutes.
10. The preparation method according to claim 8, characterized in that: In step (3), the temperature of the water bath is 35-45° C., the time for ultrasonic dissolution in the water bath is 8-15 min, the time for ultrasonic dissolution in the water bath is continued to be 10-30 min, the time for stirring in the water bath is 8-15 min, and the time for aging is 20-50 min; in step (4), the time for stirring is 5-10 min, and the time for stuffing is 2-10 min; in step (5), the time for rapid stirring is 8-10 min.
Citation Information
Patent Citations
Method for preparing light fly ash based heat insulating material
CN103936387A
Landfill impervious barrier material and preparation method thereof
CN110668773A
Vertical anti-seepage isolation ecological barrier material for contaminated site and preparation method thereof
CN112028582A
Anti-cracking low-heat-transfer enhanced vertical blocking barrier material as well as preparation method and application thereof
CN112374807A
Impermeable material and preparation method thereof
CN112430046A
Cited By
Modified steel slag-bentonite-based premixed fluid soil and preparation method thereof
CN122562469A